Clinical characteristics and outcome of children hospitalized with scrub typhus in an area of endemicity - Wangrangsimakul, T; Greer, R; Chanta, C; Nedsuwan, S; Blacksell, S; Day, N; Paris, D (Oxford University Press, 2019)
Background Scrub typhus, caused by Orientia tsutsugamushi, is a major cause of acute febrile illness in children in the rural tropics. Methods We recruited 60 febrile pediatric patients with a positive scrub typhus rapid diagnostic test result and 40 healthy controls from Chiang Rai Province in northern Thailand. Diagnosis was confirmed by the detection of (1) O. tsutsugamushi–specific DNA in blood or eschar samples with a polymerase chain reaction assay, (2) a fourfold rise in immunoglobulin M (IgM) titer to ≥1:3200 in paired plasma samples with an indirect immunofluorescence assay (IFA), or (3) a single IgM titer of ≥1:3200 in an acute plasma sample with an IFA. Demographic, clinical, and laboratory data were collected, and patients were followed up for 1 year. Results Diagnosis was confirmed in 35 (58%) of 60 patients, and all controls tested negative for scrub typhus. Patients with confirmed scrub typhus had clinical symptoms, including fever (35 of 35 [100%]), eschar (21 of 35 [60%]), cough (21 of 35 [60%]), tachypnea (16 of 35 [46%]), lymphadenopathy (15 of 35 [43%]), and headache (14 of 35 [40%]). Only 4 (11%) of 35 patients received appropriate antibiotic treatment for scrub typhus before admission. The median fever-clearance time was 36 hours (interquartile range, 24–53 hours). Complications observed include hepatitis (9 of 35 [26%]), severe thrombocytopenia (7 of 35 [20%]), pneumonitis (5 of 35 [14%]), circulatory shock (4 of 35 [11%]), and acute respiratory distress syndrome (3 of 35 [9%]). Treatment failure, defined by failure to defervesce within 72 hours of antibiotic treatment initiation, was noted in 8 (23%) of 35 patients, and 1 (3%) of the 35 patients died. No evidence of relapse or reinfection was found. Conclusion Pediatric scrub typhus in northern Thailand is often severe and potentially fatal with delays in treatment a likely contributing factor. Additional studies to investigate the bacterial, pharmacologic, and immunologic factors related to treatment outcome along with measures to improve public awareness should be prioritized.